Exploring possibilities of social entrepreneurial activities as a tool to reduce unemployment amongst churches in Tshwane central and Mamelodi East: Pretoria case study - Manyaka-Boshielo, Semape J. (HTS teologiese studies, 2017)
Unemployment is one of the major problems in South Africa. It is the concern of the government and the people at large to engage in means in order to reduce poverty. In this research, I would like to explore the possibilities of social entrepreneurial activities as a way of social and economic transformation in Tshwane. If this could be a possibility it means the church can go all out to see that the communities and members are encouraged to engage in. People will be able to improve their lives without depending on the grants from the government. Our methodology will be a literature review and intra-disciplinary approach. The method would be community mapping, World Café and focused group.